Fishes and Macroinvertebrates of Bago River, Negros Occidental, Philippines - Bucol, Abner A.; Pacalioga, Jessica O.; Linaugo, Joji D.; Menes, Carmen C.; Patiluna, Ma. Lotus E.; Turbanos, Ferdinand M. (Silliman Journal, 2022)
5IFmTIFTBOENBDSPJOWFSUFCSBUFTPG#BHP3JWFSXFSFTVSWFZFEGPSthree months each during wet (July, August, and September 2009) and dry (February, March, and April 2010) seasons to establish baseline data on species composition and distribution. Collection PGmTIFTBOENBDSPJOWFSUFCSBUFTNBEFVTFPGBWBSJFUZPGHFBST including cast net, gill net, hook and line, and two indigenous gears called “garab” and “taon”, supplemented by hand picking. Within UIFTJYNPOUIQFSJPE mTIFT BOEBRVBUJDNBDSPJOWFSUFCSBUFT XFSFDPMMFDUFEBOEJEFOUJmFE#BHP3JWFSEJWFSTJUZJTEPNJOBUFE in terms of abundance by introduced species. The study made a DPNQSFIFOTJWFMJTUPGmTIFTBOENBDSPJOWFSUFCSBUFTPG#BHP3JWFS